KEKABURAN HAK PENANAM MODAL DI IBU KOTA NUSANTARA BERDASARKAN PERATURAN PEMERINTAH NOMOR 12 TAHUN 2023 - Maharani, Made Novia; Apryani, Ni Wayan Ella (Kertha Negara : Journal Ilmu Hukum; Vol 12 No 10 (2024), 2025)
The fundamental aim of this research is to examine the extent of investors' rights in light of Law No. 25 of 2007 and Government Regulation No. 12 of 2023, as well as to investigate the implications of the renewal of investors' rights in Government Regulation No. 12 of 2023 on economic development in the Nusantara Capital. This research employs a normative research method to analyze the legal materials used. In addition, a statutory approach is applied in structuring the study. The research findings reveal that there are several differences in the investors' rights between Law No. 25 of 2007 and Government Regulation No. 12 of 2023, such as the right to ownership of business fields. Article 77 of Law No. 6 of 2023, which amends Article 12 paragraphs (1) and (2) of Law No. 25 of 2007, clearly regulates which types of businesses can be undertaken by investors. The renewal of investors' rights in Government Regulation No. 12 of 2023 concerning the ease of business licensing in the Nusantara Capital area is expected to boost investment, develop the MSMEs and Cooperative sectors, accelerate infrastructure development, create new job opportunities, and increase the population.